THE URGENCY OF SENSITIVITY TO SOCIAL PROBLEMS IN THE COMMUNITY ENVIRONMENT BASIC SOCIAL SCIENCES COURSE OUTPUT IN UNIVERSITY - Setiawan, Bagus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research is based on the basic social sciences course given as a compulsory subject to second semester students in the social sciences department of Sayyid Ali Rahmatullah State Islamic University, Tulungagung. As a compulsory subject, the department has a big aim, namely to provide basic social knowledge to students at the end of the lecture to have, possess, various moral & social attitudes, a sense of sensitivity to the conditions of social problems that exist around students, which is considered important in the current era of society. Aoutput fromgoal basic social science courses. The main problems in this research include: 1. Do basic social science courses help TIPS UIN Sayyid Ali Rahmatullah Tulungagung students find social problems in society? 2. Are TIPS UIN Sayyid Ali Rahmatullah Tulungagung students able to provide solutions to social problems found in society ?, 3. To what extent do TIPS students at Sayyid Ali Rahmatullah Tulungagung State Islamic University consider the importance of sensitivity to social issues in society? This research was conducted at the Tadris Imu Social Sciences Study Program, Faculty of Tarbiyah and Teacher Training, UIN Sayyid Ali Rahmatullah Tulungagung State Islamic University which is located at Jalan Mayor Sujadi Timur No. 46 Plosokandang Tulungagung. The type of research used in this research is quantitative percentage researchsurvey. This research aims to see how much or how many students have, have, and consider it important that sensitivity to social problems that exist in the community where students live. The population in this study were all active students in semester 2 who were taking basic social science courses for the 2023/2024 academic year, in 3 classes, namely Tadris IPS class 2A, Tadris IPS class 2B, and Tadris IPS class 2C, with a total of 95 students. student. From the research results, problem formulation 1 is; By providing ISD courses, it can be seen that as many as 87% of TIPS students can find social problems that exist in society. Problem formulation 2; Shows that almost all students with a percentage of 80% who discover social problem phenomena in the community can provide solutions in the form of descriptions of various stages of activities, actions, and also suggestions for efforts to resolve existing social problems. Research results on problem formulation 3; shows that from the assessment scale received by students, almost 90% stated that sensitivity to social problems was considered 10% important, 90% was very important in students after receiving the Basic Social Sciences course with a description of its importance as a provider of solutions, suggestions, for various social problems that arise. exist and are discovered by students around the community. And according to students, it is also important as an effort to maintain diversity and maintain the moral values of society in the global era.